ҚАЗІРГІ ҚЫТАЙ ТІЛІНДЕГІ КӨП КОМПОНЕНТТІ АНЫҚТАУЫШ - Абдурақын, Н. (Journal of Oriental Studies, 2016)
В статье рассматривается роль и путь образованиямногокомпонентного сложного в грамматике современ-ного китайского языка.The article considers the role and ways of formation ofadjectives consisting o several parts in Moderns Chinesegrammer.